Late Traces of the Cults of Cybele and Attis. The Origins of the Kurenti and of the Pinewood Marriage (“Borovo Gostüvanje”)Pozni sledovi Kibelinega in Atisovega kulta. O izvoru kurentov in borovega gostivanja - Ciglenečki, Slavko (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The carnival mask of the kurent invokes the memory of the mythical companions of Cybele and Attis, who played an important role directly before Christianity became the prevailing religion throughout the territory of present-day Slovenia. It also seems that pinewood marriage (“borovo gostüvanje”), an event that takes place during the carnival festivities, reflects one of the high points of the March celebrations dedicated to Attis. The author further mentions some additional elements of the heritage which have preserved the elements of the Great Mother cult as late as the Middle Ages and even into modern times.